Relation between gestational anemia and postpartum depression - Amir -Ali- Akbari, S; Asl- Tooghiri, M; Kariman, N; Alavi- Majd, H (Advances in Nursing & Midwifery, 2009)
Abstract Introduction: Women at child-bearing age are at risk of postpartum depression. This disease results in serious complications for the mother, infant and family. The cause of depression is not clear. Various studies indicate some effect of psychosocial factors in this regard but little information is available about biological factors. Purpose: This analytical prospective study was carried out to determine the relation between anemia and postpartum depression in pregnant women referring to Fatemiye Healthcare Center affiliated to Hamadan Medical University in 2006. Materials and Methods: 159 pregnant women were selected by purposive sampling method. Their blood samples were collected to check anemia between 38-40 weeks of gestation after their informed consent. They were then divided into two anemic (89 subjects) and non-anemic (70 subjects) groups and matched in terms of their characteristics. Subjects in both groups completed Edinburgh questionnaire on 28th day after delivery for postpartum depression. Chi-square¸ Mann-Whitney U and relative-risk tests were used to analyze data. Results: %14.6 in the non-anemic group and %38.6 in the anemic group were depressed at 38-40 weeks of pregnancy and, in this period, anemia increased the probability rate of depression by 1.8 times (P<0.05). A significant relation was also found between the severity of anemia and postpartum depression (P<001). Conclusion: It seems that there is a significant relation between anemia as well as its severity at 38-40 weeks of pregnancy and postpartum depression. It is recommended that women with gestational anemia receive more accurate checkups and better follow-up for postpartum depression to take necessary treatment. Key words: Postpartum depression, Hemoglobin, Anemia.